Epididymis incision as a method to collect epididymal sperm cells in alpacas. Issue 1 (7th December 2021) - Auer, Marlen; Wagner, Henrik; Failing, Klaus; Wehrend, Axel
Abstract: Background: Epididymal sperm can be collected post‐castration or post‐mortem. This method has already been described for alpaca ( Vicugna pacos ), but little data are available on success rate and the influence of diluent on it. Objective: The aim was to investigate the effectiveness of epididymis incision as an extraction method. Method: Post‐castration epididymides (n = 78) were incised and semen was collected from cut surfaces. Further sperm were flushed with two semen extenders. For the left epididymis, a diluent without animal proteins and for the right, a diluent with egg yolk was utilised. Collected sperms were immediately spermatologically examined. Results: Due to incorrect measurements, the samples of seven epididymides were not analysed. An evaluation was possible in 58 samples. Average density was 108.80 ± 83.28 million/mL and motility was 53.30 ± 18.17%. On average, 76.70 ± 11.60% of the sperm were vital in eosin‐stained specimens. In the hypoosmotic swelling test, an average of 69.50 ± 10.48% of the sperm had an intact plasma membrane. Semen extender had no effect on spermatological parameters (p > 0.05). Overall success rate of sperm recovery was 83%. Extraction of epididymal sperm was possible in 68.80% of the 2‐year‐old males. The 13 epididymides from which no sperm recovery was possible were histologically examined and for 10, there was no histological evidence of sperm. The corrected success rate was 95.60%. Conclusion: Testicular volume (p = 0.0453), but not age (p = 0.62), had an effect on the probability of obtaining sperm. Abstract : In this study, sperm extraction by incision of the alpaca epididymis was investigated to reduce contamination and enable spermatological investigation by CASA. Besides, the influence of two diluents, testicle volume and age on sperm quality and collection rate was determined.